Profile of Abdominal Trauma Patient Underwent Surgery in Emergency Operating Room of Sanglah General Hospital from January until December 2015 - Halim, Reza; Sueta, Made Agus Dwianthara (JBN (Jurnal Bedah Nasional), 2018)
Objective: to investigate the characteristics of patients, presentation of the abdominal organ that involved, and clinical data associated with this event. Methods: this is a descriptive study with retrospective design. Total samples were all patients with abdominal trauma who underwent surgery on the emergency operating theatre of Sanglah General Hospital between January and December 2015. Baseline data of patients were obtained from the medical records. Results: within the study period, a total of 104 patients with abdominal trauma who underwent surgery in the emergency operating room of Sanglah General Hospital were identified. Man comprised 87.5% of the patients and mostly were 17-45 years old (75%). The motor vehicle accident occurred majority on the weekend (65%). Liver and spleen were the most affected organ (55%). Splenectomy (35%) and liver repair surgery (33%) were the most often performed procedures. Conclusion: Abdominal trauma caused by motor vehicle accident occurred mostly on the weekend. Two most affected organs in abdominal trauma were liver and spleen. Splenectomy and liver repair surgery were the procedures performed for these trauma patients.